2021
DOI: 10.1002/zaac.202100027
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Hirshfeld Surface Analysis of Trimethoxy(1‐naphthyl)silane – Intermolecular Interactions in a One‐Component Single‐Crystalline Trimethoxysilane

Abstract: Weak intermolecular interactions play a major role in structure formation of molecular crystals. Trimethoxy(1-naphthyl)silane ( 1), the first one-component single-crystalline trimethoxysilane, was analyzed by single-crystal X-ray diffraction. Weak intermolecular interactions were studied by Hirshfeld surface analysis along with 2D fingerprint plots. Both C(methyl)À H•••C and C(naphthyl)À H•••C interactions were found. A C(naphthyl)À H•••O hydrogen bond between a silicon-bound methoxy oxygen and an aromatic hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Since we expect the anisotropic C−H⋅⋅⋅O and C−H⋅⋅⋅C(π) contacts to be the strongest intermolecular interactions in the crystal structure of 4 , it can be assumed that the short H⋅⋅⋅H contacts result from a favorable molecular pre‐orientation caused by C−H⋅⋅⋅O and C−H⋅⋅⋅π hydrogen bond‐driven supramolecular synthon formation, [26] similar to the part of the crystal structure shown in Figure 3 (left). Compared to the previously and thoroughly investigated crystal structure of (1‐naphthyl)trimethoxysilane, [8c] it becomes apparent that the anisotropic H⋅⋅⋅C and H⋅⋅⋅O contacts in compound 4 are less pronounced, but H⋅⋅⋅H interactions are all the more important.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Since we expect the anisotropic C−H⋅⋅⋅O and C−H⋅⋅⋅C(π) contacts to be the strongest intermolecular interactions in the crystal structure of 4 , it can be assumed that the short H⋅⋅⋅H contacts result from a favorable molecular pre‐orientation caused by C−H⋅⋅⋅O and C−H⋅⋅⋅π hydrogen bond‐driven supramolecular synthon formation, [26] similar to the part of the crystal structure shown in Figure 3 (left). Compared to the previously and thoroughly investigated crystal structure of (1‐naphthyl)trimethoxysilane, [8c] it becomes apparent that the anisotropic H⋅⋅⋅C and H⋅⋅⋅O contacts in compound 4 are less pronounced, but H⋅⋅⋅H interactions are all the more important.…”
Section: Resultsmentioning
confidence: 72%
“…For comparison, in tert ‐butylfluorodiphenylsilane, [11b] the shortes H⋅⋅⋅C contacts also use the tert ‐butyl group as C−H donor and can be attributed to edge‐shifted C(methyl)−H⋅⋅⋅C(π) contacts, which, in addition to C−H⋅⋅⋅F−Si contacts, represent the most important directional interactions in the fluorine derivative. Although the C−H donor ability decreases in the series C(sp)−H>C(sp 2 )−H>C(sp 3 )−H, [18] aliphatic C−H groups are known to be significantly involved in stabilizing the crystal structure via attractive C−H⋅⋅⋅π interactions [8c,19] . Regarding the nature of the interaction, it was found that C−H⋅⋅⋅π interactions are dominated by dispersion rather than electrostatic contributions [20]…”
Section: Resultsmentioning
confidence: 99%
“…A secondary lithium amide was prepared by deprotonation of the respective secondary amine with n -butyllithium in n -pentane and subsequently reacted with the appropriate di- and trimethoxysilanes over a period of 20 h at room temperature. It was deduced from density functional theory (DFT) calculations that metal effects are crucial for a correct description of the unusual thermodynamics of the reaction shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the larger wing reflects C–H⋯π interactions where the C–H bonds point more toward the edge of the phenyl ring. 18…”
Section: Resultsmentioning
confidence: 99%